Desain Kurikulum dan Bahan Ajar Bahasa Arab yang Menarik dan Efektif - Aisyah; Hasan, Laili Mas Ulliyah (Global Action and Education for Society, 2024)
This article reviews the design of an effective and interesting Arabic curriculum and teaching material, aimed at improving students' understanding and skills in the language. The main focus is on the creation of curricula that are dynamic and responsive to student needs, as well as the development of educational materials that vary and utilize technology. The methodology described includes the analysis of students' needs to design a competence-based curriculum, the integration of technology into the teaching material, and the use of interactive media to create an exciting learning experience. Implementation of these curricula and teaching materials shows positive results, with significant increases in student motivation and involvement, as well as improvements in their language skills. Continuous evaluation and adjustment based on student feedback are key to ensuring that the curriculum and the teaching material remain relevant and effective. This article provides insight into how a systematic approach to curriculum design and the development of teaching materials can improve the quality of Arabic learning and meet student learning needs in a comprehensive way.